IoT-BASED AUTOMATIC PET FEEDER CONTROL SYSTEM - YATSYSHYN, MAXIM; PETRUSHAK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article presents the development of an IoT system for automatic control of a pet feeder using the ESP32 microcontroller and the Blynk cloud platform. The selection of hardware components for data collection, processing, and transmission is substantiated. The system’s structural diagram, operation principles, control algorithms, and examples of integration with humidity, temperature, motion, and water level sensors are provided. A detailed analysis of wireless communication protocols within the context of IoT solutions is also conducted. The current development of IoT technologies opens up great opportunities for automating household tasks, including pet care. Pet owners often face the problem of lack of constant monitoring of food, water availability, and the general condition of the animal’s environment. Therefore, it is important to create an intelligent feeding system with remote access and monitoring of environmental parameters. According to, IoT platforms must meet the requirements of scalability, security, energy efficiency, and integration. Solutions based on ESP32 are among the most popular in the smart home industry due to built-in Wi-Fi, Bluetooth, and low power consumption. At the same time, the Blynk platform makes it easy to implement a control and monitoring interface via a smartphone, providing convenience for the end user. The aim of the work is to develop an inexpensive and reliable IoT feeder control system that allows remote control of the animal feeding process and provides automatic response to changes in climatic conditions in its environment. To communicate with the cloud, the Blynk platform is used, which provides a user interface for viewing the status of sensors and controlling devices. Information is transmitted via Wi-Fi in real time.